Penggunaan Google Forms Untuk Pembuatan Soal Ujian Sekolah di SMK Lowis Sakti - Masbullah; Salmi Yuniar Bahri (Yayasan Literasi Sains Indonesia, 2022)
At this time the strategy in learning during the Covid-19 pandemic is through online learning. Google Forms is one solution, especially in making school exam questions. The use of Google Forms is increasing from time to time. This service from Google can be used for various purposes, such as creating forms, questionnaires, to creating questions. Creating questions is one of the Google Form features that are often used by academics, be it teachers, lecturers, students, researchers, and so on. The implementation of this community service aims to improve the insight and skills of teachers in choosing the right learning media during Distance Education. Partners involved in this community service activity are teachers at SMK Lowis Sakti, where the activities carried out are exam questions using the Google Form application, and the results of the two-day training were seen by teachers at SMK Lowis Sakti enthusiastic about the material presented. and have been found and able to answer questions and practice directly using the Google Form application.